Toxic plants of livestock interest in municipalities of the microregion of Alto Médio Gurguéia - Piauí - Pinho de Sousa, Caike; Rodrigues de Amorim, Wenderson; do Nascimento Martins, Gabriel; Rodrigo Sousa Soares Santos, Alan; de Sousa Sá, Isael; Vieira Dada, Julia Morgana; Reis de Carvalho, Sávio Matheus; Martins Alves, Mayara Jane; Rodrigues da Silva, Italo Carlos; Gomes Dantas, Jackson Brendo; Veras de Almeida, Joyce; Escórcio Pinheiro, Raizza Eveline; et al. (Pubvet, 2020)
This study aimed to conduct a survey of the main toxic plants of livestock interest in municipalities of the microregion of the Alto Médio Gurguéia, state of Piauí, Brazil. Visits were made to farms, to assistance agencies to rural producers (Agência de Defesa Agropecuária do Piauí - ADAPI and Instituto de Assistência Técnica e Extensão Rural do Piauí - EMATER) and Educational Institutions (Campus Professora Cinobelina Elvas – CPCE and Colégio Técnico de Bom Jesus – CTBJ, both linked to Universidade Federal do Piauí – UFPI) during the months of May and June 2017. Forms adapted for conducting the interviews were used. The total number of interviewees was 60 people, who resided or provided technical assistance in the region. The sample comprised nine municipalities in the microregion of the Alto Médio Gurguéia. All the plants listed in the form were cited at least once by the interviewees; however, the most mentioned ones were prioritized. Plants like Manihot spp. 78,3%, S. coriaceum 55%, Brachiaria spp. 43,3%, E. contortisiliquum 41,7%, M. pseudoglaziovii 25%, D. mollis Benth 14,3%, M. indica 7,1% e D. ecastophyllum 7,1% were presented as toxic in the region. Similar results were found in municipalities belonging to the micro region of the Cariri, state of Ceará. It can be concluded that plants with toxic potential in the microregion of the Alto Médio Gurguéia is the plant Manihot spp. 78,3%, followed by the plants S. coriaceum 55%, Brachiaria spp. 43,3%, E. contortisiliquum 41,7%, M. pseudoglaziovii 25%, D. mollis Benth 14,3%, M. indica 7,1% and also the plant called D. ecastophyllum 7,1%
Keywords: Intoxication; animal production; South Piauí